2023
DOI: 10.3390/antiox12111998
|View full text |Cite
|
Sign up to set email alerts
|

Selection, Identification, and Transcript Expression Analysis of Antioxidant Enzyme Genes in Neoseiulus barkeri after Short-Term Heat Stress

Tong Zhu,
Weizhen Li,
He Xue
et al.

Abstract: Phytoseiid mite Neoseiulus barkeri is a crucial biological control agent utilized to control pest mites and many insects in crops all over the world. However, they are vulnerable to multiple environmental pressures, with high-temperature stress being the most significant challenge. Heat stress disrupts the balance of reactive oxygen species (ROS) levels in organisms, resulting in oxidative stress within the body. Antioxidant enzymes play a crucial role in effectively neutralizing and clearing ROS. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The relative expression levels of the six GST genes increased significantly after exposure to heat stress, especially at 42 • C. Among them, the relative expression levels of TuGSTm1, TuGSTm2, TuGSTd1, and TuGSTd2 reached the highest level after 6 h exposure at 42 • C, and the relative expression levels of TuGSTm3 and TuGSTo reached the highest level after 2 h exposure at 42 • C. We supposed that the potential reason for the disparity between the different recombinant GSTs in the time taken to reach the highest expression is the different affinity for the substrate. Excessive temperatures can cause oxidative stress in organisms [48]. Our previous results showed that short-term heat shock could cause oxidative stress in T. urticae, and the activities of three antioxidant enzymes (SOD, Prx, and CAT) and total antioxidant capacity (T-AOC) were significantly increased [9].…”
Section: Discussionmentioning
confidence: 95%
“…The relative expression levels of the six GST genes increased significantly after exposure to heat stress, especially at 42 • C. Among them, the relative expression levels of TuGSTm1, TuGSTm2, TuGSTd1, and TuGSTd2 reached the highest level after 6 h exposure at 42 • C, and the relative expression levels of TuGSTm3 and TuGSTo reached the highest level after 2 h exposure at 42 • C. We supposed that the potential reason for the disparity between the different recombinant GSTs in the time taken to reach the highest expression is the different affinity for the substrate. Excessive temperatures can cause oxidative stress in organisms [48]. Our previous results showed that short-term heat shock could cause oxidative stress in T. urticae, and the activities of three antioxidant enzymes (SOD, Prx, and CAT) and total antioxidant capacity (T-AOC) were significantly increased [9].…”
Section: Discussionmentioning
confidence: 95%